Reservoir quality controls on Rotliegend fluvio-aeolian wells in Germany and the Netherlands, Southern Permian Basin – Impact of grain coatings and cements. (February 2020) - Busch, Benjamin; Hilgers, Christoph; Adelmann, Dirk
Abstract: Reservoir quality in sandstones can be a function of temperature, pressure, and chemical alterations over time. Some intrinsic properties of sandstones can additionally impact the evolution of reservoir quality. The detrital composition, depositional environment, and properties controlled thereby, dictate some of the diagenetic changes. Extrinsic processes, like external fluids, e.g. from hydrothermal events or dewatering of clay minerals, can additionally result in changes of reservoir quality. One of these properties are grain coatings on quartz grains, which can strongly affect pore cementation by quartz overgrowths. To predict and infer the quality of undrilled reservoirs, constraints are needed to predict their occurrence. We analyse two reservoir settings in the Southern Permian Basin and delineate the impact of depositional systems, lithologies, detrital and authigenic composition on reservoir quality and with regard to grain coatings. Results highlight the importance of diagenetic alterations and the source area in regards to burial development in different parts of the Southern Permian Basin. Samples from the Rotliegend Bahnsen Sandstone Member from Germany and the Slochteren Sandstone Formation from the Netherlands have been petrographically and petrophysically analysed and linked to depositional environments. Our data shows that the emplacement and presence of grain coating minerals cannot be simply linked to the depositional environment or processes controlled thereby (e.g. grain size and sorting), neither on a reservoir-, nor on a basin scale. The dissolution of alumosilicates additionally has no consistent impact on the authigenesis of chloritic grain coatings on the reservoir- or basin scale in this study. This implies the necessity of sample specific analyses and importance of the assessment of diagenetic alterations when analysing, modelling, or predicting reservoir quality in similar settings worldwide. Highlights: Grain coatings in diagenetically overprinted Rotliegend sandstones do not correlate with grain sizes, sorting or the depositional environment. Diagenetic overprints strongly alter the grain coating distribution. Reservoirs experiencing a lower thermal exposure during burial can be good reservoirs, regardless of grain coating coverages.